FENOMENA GAMBARAN PERILAKU KORUPTIF MAHASISWA AKUNTANSI - Aryani, Habsyah Fitri; Ersyafdi, Ilham Ramadhan (Jurusan Akuntansi Politeknik Negeri Pontianak, 2024)
This study is a descriptive study which aims to describe the phenomenon of corrupt behavior with the respondents being accounting students. This study uses a mixed method by combining quantitative instruments, namely interviews and questionnaires and taking information about the phenomena studied based on previous scientific articles which is a qualitative approach. The results of the study found that there were two out of ten examples of corrupt behavior that were most frequently carried out or obtained a percentage score above 51% of the total respondents, namely cheating at 78.79% and copying (copy pasting) work in the form of assignments/exams from the internet at 87.88 %. Meanwhile, the remaining eight behaviors get a percentage below 51%. Apart from that, there are also two examples of corrupt behavior that have never been carried out at all, namely manipulating activity accountability reports and falsifying scholarship data. If we look at each individual, the majority of respondents have committed two and three of the ten examples of corrupt behavior, which when combined gets a percentage above 51%, namely 57.57%. Based on interviews, many respondents used rationalization reasons regarding this corrupt behavior so that special learning was needed at universities to straighten out respondents' understanding, such as requiring anti-corruption education courses.